2012
DOI: 10.1111/j.1439-0531.2012.02056.x
|View full text |Cite
|
Sign up to set email alerts
|

Domestic Animal Models for Biomedical Research

Abstract: Contents Experimental animals in biomedical research provide insights into disease mechanisms and models for determining the efficacy and safety of new therapies and for discovery of corresponding biomarkers. Although mouse and rat models are most widely used, observations in these species cannot always be faithfully extrapolated to human patients. Thus, a number of domestic species are additionally used in specific disease areas. This review summarizes the most important applications of domestic animal models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(47 citation statements)
references
References 206 publications
(306 reference statements)
0
47
0
Order By: Relevance
“…Maternal mass can increase by more than 50% during gestation. The Guinea pig is a widely used model to study human physiology; and results regarding various facets of their reproductive biology have been used to assess broad questions that pertain to other mammal species (Bahr & Wolf, 2012). For instance, the effects of prenatal stress on reproductive parameters, including sexual steroid concentrations have been recently examined in Guinea pigs (Schöpper et al, 2012a, b).…”
Section: Study Speciesmentioning
confidence: 99%
“…Maternal mass can increase by more than 50% during gestation. The Guinea pig is a widely used model to study human physiology; and results regarding various facets of their reproductive biology have been used to assess broad questions that pertain to other mammal species (Bahr & Wolf, 2012). For instance, the effects of prenatal stress on reproductive parameters, including sexual steroid concentrations have been recently examined in Guinea pigs (Schöpper et al, 2012a, b).…”
Section: Study Speciesmentioning
confidence: 99%
“…In addition, as dogs are still readily used as experimental animals in a wide array of biomedical applications [16], the discovery of a new sense would have far reaching consequences also in this sector.…”
Section: Introductionmentioning
confidence: 99%
“…This includes many species, such as cows and pigs, that have significant economic value and often detailed pedigree information [101,102]. For example, Braunschweigh et al has demonstrated that male pigs (boars) fed a diet to induce hypermethylation have F2 offspring with decreased adiposity [103].…”
Section: Transgenerational Effects On Metabolic Disease In Model Omentioning
confidence: 99%